Fluorescent metal quantum clusters: an updated overview of the synthesis, properties, and biological applications - Khandelwal, Puneet; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
Metal quantum clusters are evolving as excellent systems for a wide range of biological applications due to their small size (similar to 2 nm), tunable optical properties, including optical absorption, photoluminescence (UV to NIR), nonlinear optical properties (two-photon absorption, two-photon fluorescence, and second/third harmonic generation), ultrafast dynamics (relaxation kinetics, electron-phonon coupling, and radiative emission), and magnetism. These excellent properties have resulted in their use in a broad range of applications, including the sensing of ions (heavy metal ions, anions), biomolecules (proteins, DNA, miRNA, and enzymes), biological cells, diagnosis, and therapy. This article presents an introduction to metal quantum clusters, including a brief history of research in this system and an overview of the existing theories to understand their properties. We also discuss the synthesis methods, the various properties of quantum clusters and present a broad and updated overview of the applications of metal quantum clusters in biology.